The mesenchymal stem cells in multiple sclerosis (MSCIMS) trial protocol and baseline cohort characteristics: an open-label pre-test: post-test study with blinded outcome assessments - Connick, Peter; Kolappan, Madhan; Patani, Rickie; Scott, Michael A; Crawley, Charles; He, Xiao-Ling; Richardson, Karen; Barber, Kelly; Webber, Daniel J; Wheeler-Kingshott, Claudia AM; Tozer, Daniel J; Samson, Rebecca S; et al. (Current controlled trials in cardiovascular medicine, 2011)
Background No treatments are currently available that slow, stop, or reverse disease progression in established multiple sclerosis (MS). The Mesenchymal Stem Cells in Multiple Sclerosis (MSCIMS) trial tests the safety and feasibility of treatment with a candidate cell-based therapy, and will inform the wider challenge of designing early phase clinical trials to evaluate putative neuroprotective therapies in progressive MS. Illustrated by the MSCIMS trial protocol, we describe a novel methodology based on detailed assessment of the anterior visual pathway as a model of wider disease processes - the "sentinel lesion approach". Methods/design MSCIMS is a phase IIA study of autologous mesenchymal stem cells (MSCs) in secondary progressive MS. A pre-test : post-test design is used with healthy controls providing normative data for inter-session variability. Complementary eligibility criteria and outcomes are used to select participants with disease affecting the anterior visual pathway. Results Ten participants with MS and eight healthy controls were recruited between October 2008 and March 2009. Mesenchymal stem cells were successfully isolated, expanded and characterised in vitro for all participants in the treatment arm. Conclusions In addition to determining the safety and feasibility of the intervention and informing design of future studies to address efficacy, MSCIMS adopts a novel strategy for testing neuroprotective agents in MS - the sentinel lesion approach - serving as proof of principle for its future wider applicability. Trial registration ClinicalTrials.gov ( NCT00395200 ).